Neurocognitive outcome in children with sickle cell disease after myeloimmunoablative conditioning and haploidentical hematopoietic stem cell transplantation: a non-randomized clinical trial - Braniecki, Suzanne; Vichinsky, Elliott; Walters, Mark C.; Shenoy, Shalini; Shi, Qiuhu; Moore, Theodore B.; Talano, Julie-An; Parsons, Susan K.; Flower, Allyson; Panarella, Anne; Fabricatore, Sandra; Morris, Erin; et al. (Frontiers in Neurology, 2024)
Background Due to the risk of cerebral vascular injury, children and adolescents with high-risk sickle cell disease (SCD) experience neurocognitive decline over time. Haploidentical stem cell transplantation (HISCT) from human leukocyte antigen-matched sibling donors may slow or stop progression of neurocognitive changes. Objectives The study is to determine if HISCT can ameliorate SCD-associated neurocognitive changes and prevent neurocognitive progression, determine which specific areas of neurocognitive functioning are particularly vulnerable to SCD, and determine if there are age-related differences in neurocognitive functioning over time. Methods We performed neurocognitive and neuroimaging in SCD recipients following HISCT. Children and adolescents with high-risk SCD who received parental HISCT utilizing CD34+ enrichment and mononuclear cell (T-cell) addback following myeloimmunoablative conditioning received cognitive evaluations and neuroimaging at three time points: pre-transplant, 1 and 2 years post-transplant. Results Nineteen participants (13.1 ± 1.2 years [3.3–20.0]) received HISCT. At 2 years post-transplant, neuroimaging and cognitive function were stable. Regarding age-related differences pre-transplantation, older children (≥13 years) had already experienced significant decreases in language functioning (p < 0.023), verbal intelligence quotient (p < 0.05), non-verbal intelligence quotient (p < 0.006), and processing speed (p < 0.05), but normalized post-HISCT in all categories. Conclusion Thus, HISCT has the potential to ameliorate SCD-associated neurocognitive changes and prevent neurocognitive progression. Further studies are required to determine if neurocognitive performance remains stable beyond 2 years post-HISCT. Clinical trial registration: The study was conducted under an investigator IND (14359) (MSC) and registered at clinicaltrials.gov (NCT01461837).